Leadership Attributes Good vs. Bad– Lessons from Vidur Neeti (Mahabharata) - Anamika Patel (International Journal of Religious and Cultural Studies, 2020)
The vast ocean of Indian Santana scriptures contains a lot more gems of wisdom for the modern era than they are accounted for. One such deep sea of knowledge is Vidur Neeti, given in Mahabharata. Vidur Neeti, mentioned in the third chapter of Udyog Parva of Mahabharata, contains the age-old wisdom which offers new insights every time anyone explores the depths of its pages. Prajaagara Parva- a subsection of Udyog Parva, includes a dialogue between King Dhritarashtra, and Prime-minister Vidur wherein Vidur advises the king about the proper code of conduct. The paper lists those verses which describe wise and foolish qualities, which can be attributed to a good and bad leader, respectively.